Determination of the Effects of Biopesticides (at Several Lethal Concentrations) from Dioscorea bulbifera L. Leaf Extract Against Cryptotermes cynocephalus Light - Oksari Ade Ayu; Uzhmiyyah Rohmatul; Susanty Devy; Rizki Fathan Hadyan; Arinana Arinana; Wanda Irvan Fadli; Lailaty Intani Quarta; Dadang Dadang (BIO Web of Conferences)
Dioscorea bulbifera leaves contain secondary metabolite compounds that can potentially control Cryptotermes cynocephalus. Preliminary tests show the toxicity of D. bulbifera leaf extract as a bioinsecticide, but further tests need to be carried out based on the results obtained. This research aims to determine the toxicity of further D. bulbifera leaf extract tests based on solvents and concentration range variations. The study used six treatments and five replications in a completely randomised design. This study used the multilevel maceration method to use three distinct polarity and lethal concentrations of solvent. Based on the results of variance analysis, it was found that variations in solvent and concentration had a significant influence on the retention value of the extract. Differences in the solvent substantially affected the degree of damage, mortality, and test weight loss. The D. bulbifera leaf methanol extract with a concentration of 6.98% of 1.2080 kg/m3 had the best retention value. Based on the test weight reduction, degree of damage, and mortality rates, the methanol extract of D. bulbifera leaves had the best results, coming in at 95.84%, 20.30%, and 294.71%, respectively. Methanol extract of D. bulbifera leaves with an LC 90 (6.98%) is efficient in controlling C. cynocephalus.